Effects of End Mill Helix Angle on Accuracy for Machining Thin-Rib Aerospace Component - Raja Abdullah, Raja Izamshah; Yuhazri, Yaakob; Mohd , Hadzley; Mohd , amran; Sivarao, Subramonian (Trans Tech Publications, 2013)
Accuracy of machined component is one of the challenging tasks for manufacturer. In the aerospace industry, machining process is widely used for fabrication of unitized-monolithic component that contains a thin-walled structure. During machining, the cutting forces cause deflection to the thin-wall section, leading to dimensional form errors that cause the finished part to be out of specification or failure. Most of the existing research for machining thin-wall component only concentrated on the process planning and the effects of cutter geometric feature is often neglected. Tool geometric feature has a direct influence on the cutting performance and should not be neglected in the machining consideration. This paper reports on the effect of helix angle on the magnitude of wall deflection. The established effects will be used for the development of high performance cutting tool for specifically machining thin-wall component.